19.4: Pixel‐Level Color Measurement Used for MicroLED Inspection Based on Imaging Spectrometer. (26th August 2021) - Luo, Shiwen; Hong, Zhikun; Zheng, Zengqiang; Zhao, Biao; Yin, Zhengzheng; Zheng, Jiong
Abstract : With the development of MicroLED technology, MicroLED displays show attractive potential because of high brightness, high efficiency, low energy consumption and long lifetime. However, it's difficult to deal with MicroLED displays' defect inspection and color measurement because MicroLED displays usually contain millions of pixels which emit light separately. In this paper, pixel‐level color measurement based on imaging spectrometer is introduced which can be used for MicroLED inspection. The imaging spectrometer offers high color measurement accuracy under different conditions including luminance, spectral shape, bandwidth. Compared with colorimeter based on color camera, the imaging spectrometer offers better accuracy and robustness.